Elastic metamaterial-based impedance-varying phononic bandgap structures for bandpass filters. (29th September 2015) - Lee, Hyung Jin; Lee, Joo Kyung; Kim, Yoon Young
Abstract: In this study, we propose a novel impedance-variation scheme in a half-quarter-wave stack (HQWS) structure to achieve desired bandpass filtering performances such as quasi-flat tops, steep bandedges and wide surrounding bandgaps. Specifically, only the characteristic impedances of constituent half-wave layers are varied without altering the phase shift of π at the center frequency of the target passband that is the Fabry–Perot resonance frequency of the unperturbed original HQWS structure. Because the simultaneous control of characteristic impedance and phase shift in each of the constituent half-wave layers is not achievable only by layer-sizing, the varied layers must be realized by metamaterials. So, specially-configured aluminum-based metamaterials having a double-slit void inhomogeneity are engineered and the actual wave transmission performance of the metamaterial-realized HQWS structure is examined numerically and experimentally.